TRANSLATOR TRAINING BY DISTANCE LEARNING — A DUAL APPROACH1 - Karnedi, Karnedi (Indonesian Journal of Applied Linguistics, 2015)
A variety of approaches have been adopted by institutions of higher education offering programmes in translator training. Some of these approaches are centred on early training; while others on socio-constructivism. Presenting a facet of training that differs from those generally used in most programmes, this paper examines how task-based approaches used over the course of the curriculum and the project-based approaches adopted in the final year in the form of translation portfolio can be an integral part of an undergraduate translation programme run by distance learning. Translation students? performance while completing the project online is used as the data supported with online questionnaires. A critical analysis of these two approaches engenders a crucial discussion of increased student autonomy. The project-based translation portfolio is better suited to more advanced students, whereas task-based translation activities are for students at the early stages of training. Nevertheless, the two approaches are compatible and complementary.